The Urgency of Citizenship Education for Elementary Age Children - Atikah Zahrani Purba; Bintang Maharani Abdullah; Nita Afriani Siregar; Nurhaliza Ertays Siregar (Yayasan Zia Salsabila, 2022)
Citizenship education is a compulsory subject at all levels of education, both SD/MI, SMP, SMA, and tertiary level. Citizenship education has a very large influence in shaping the character and personality of each community so that it is in accordance with the norms and values of Pancasila. Therefore, citizenship education is very important to be taught from an early age. This study aims to find out about the nature and background of the importance of citizenship education in SD/MI. In this paper, writing uses the method of literature review. This literature review can be sourced from books, journals, or articles relevant to the subject matter. Based on this research, it shows that the nature and background of citizenship education aims to show a sense of justice in society, and people have a sense of love, homeland, and nationality so that they can establish the relationship mandated by Pancasila and the 1945 Constitution.